2018
DOI: 10.3390/ph11030065
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, In Vitro, and Initial In Vivo Evaluation of Heterobivalent Peptidic Ligands Targeting Both NPY(Y1)- and GRP-Receptors—An Improvement for Breast Cancer Imaging?

Abstract: Heterobivalent peptidic ligands (HBPLs), designed to address two different receptors independently, are highly promising tumor imaging agents. For example, breast cancer has been shown to concomitantly and complementarily overexpress the neuropeptide Y receptor subtype 1 (NPY(Y1)R) as well as the gastrin-releasing peptide receptor (GRPR). Thus, radiolabeled HBPLs being able to bind these two receptors should exhibit an improved tumor targeting efficiency compared to monospecific ligands. We developed here such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 32 publications
(46 reference statements)
2
16
0
Order By: Relevance
“…For [ 177 Lu]Lu-6, comparably promising in vitro results were obtained compared to [ 68 Ga]Ga-6. As found for the 68 Ga-labeled analog, the heterodimer [ 177 Lu]Lu-6 showed a favorable pharmacokinetic profile in mice carrying PC3 and LNCaP tumors and slightly higher uptakes in both tumor types when compared with the respective monomers, confirming the positive results obtained for [ 68 Ga]Ga-6. Furthermore, the found tumor uptakes were higher in both tumor types than in any other organ at 3 h post injection (p.i.).…”
Section: Radiolabeled Peptidic Heterodimers Developed For Improved Tusupporting
confidence: 79%
See 4 more Smart Citations
“…For [ 177 Lu]Lu-6, comparably promising in vitro results were obtained compared to [ 68 Ga]Ga-6. As found for the 68 Ga-labeled analog, the heterodimer [ 177 Lu]Lu-6 showed a favorable pharmacokinetic profile in mice carrying PC3 and LNCaP tumors and slightly higher uptakes in both tumor types when compared with the respective monomers, confirming the positive results obtained for [ 68 Ga]Ga-6. Furthermore, the found tumor uptakes were higher in both tumor types than in any other organ at 3 h post injection (p.i.).…”
Section: Radiolabeled Peptidic Heterodimers Developed For Improved Tusupporting
confidence: 79%
“…On the other hand, highly rigid linkers could limit the motility of the molecule, impeding the first peptide to bind although the second binder might be forced to stay near the cell surface, increasing its binding probability. However, an effect of linker rigidity on the peptide-receptor interaction of peptide homo-or heterodimers-although having been investigated in some studies-could not be shown thus far [59,62,66,68].…”
Section: Influence Of Molecular Design On Target Interactionmentioning
confidence: 97%
See 3 more Smart Citations